Relative feeding value of three forage-based diets for Holstein heifers - Shirley, John E.; Morrill, J.L.; Carinder, W.H. (Kansas Agricultural Experiment Station, 2012)
Soybeans interseeded with grain sorghum and harvested as a mixed forage silage crop can be used successfully as a feed for growing dairy heifers. However, daily gain is greater when grain sorghum silage plus alfalfa hay or prairie hay supplemented with milo grain and soybean meal is fed.Replacement heifer programs should be cost effective but yield a heifer large enough to be bred to calve by 24 months of age and with a well developed mammary gland relatively free of internal fat. A daily gain of 1.6 to 1.8 lbs appears to be optimum to achieve the desired bodyweight to be bred by 14 months of age. Feed cost to achieve the above physical goals often accounts for 60% of the total cost in a replacement heifer program. Forage may constitute the majority of a heifer's dry matter intake during the growing phase, if it supplies adequate energy, protein, mineral, and vitamins. Grain sorghum silage and prairie hay are abundant feed sources in Kansas and are frequently used in the diets of replacement heifers. However, grain sorghum is relatively low in protein, deficient in calcium, low in potassium, and potentially adequate in energy for growing heifers diets, whereas prairie hay is adequate in potassium, low in calcium and phosphorus, marginal in protein, and low in energy. Soybeans are well adapted to Kansas conditions and offer a forage that is abundant in protein, calcium, and potassium but relatively low in energy and phosphorus. Silage composed of a mixture of soybeans and grain sorghum should provide sufficient protein, energy, calcium, phosphorus, and potassium to meet the needs of growing dairy heifers. This trial was designed to ascertain the value of soybean-grain sorghum silage relative to sorghum silage or prairie hay as a feed for growing dairy heifers.
Keywords: Dairy; Replacement heifers; Soybean meal; Grain sorghum; Milo grain